BIMBINGAN TEKNIS ORGANISASI KELURAHAN DALAM MEWUJUDKAN PEMBANGUNAN KEPEMUDAAN DIKECAMATAN TAMPAN KOTA PEKANBARU - aguswan, aguswan (Jurnal Niara, 2018)
Karang Taruna is a forum for the development of nonpartisan youth generation, which grows on the basis of awareness and sense of social responsibility from, by and for the community, especially the younger generation in the village / kelurahan or social community equally, which is mainly engaged in social welfare.Keberadaan organization Karang taruna kelurahan is the Lurah's partner in fostering and protecting the community in their respective neighborhoods. Therefore, the main task of the organization of youth is together with the Government and other community components to tackle various social welfare problems especially faced by the young generation, whether they are preventive, rehabilitative or potential youth development in their environment. on the organization of urban village cadars in the region Tampan district there is less running programs and activities that are social responsibility in the midst of society. Lack of organizational coaching and limited resources Taruna coral organization causes the functions of less efficient organisms implemented. The importance of the provision to the organization of youth can enhance the increase of knowledge and skills to the board to perform the main tasks and functions as an organization that provides social services to the community.